Everyone who can forgive me is dead : a novel - Hollander, Jenny (Minotaur Books, 2024)
"What if everything you know about the worst night of your life turns out not to be true? Nine years ago, with the world's eyes on her, Charlie Colbert fled. The press and the police called Charlie a "witness" to the nightmarish events at her elite graduate school on Christmas Eve-events known to the public as "Scarlet Christmas"-though Charlie knows she was much more than that. Now, Charlie has meticulously rebuilt her life: She's the editor-in-chief of a major magazine, engaged to the golden child of the publishing industry, and hell-bent on never, ever letting her guard down again. But when a buzzy film made by one of Charlie's former classmates threatens to shatter everything she's worked for, Charlie realizes how much she's changed in nine years. Now, she's not going to let anything-not even the people she once loved most-get in her way"--